Imigração e miséria no Brasil: o caso dos descendentes de pomeranos do município de Santa Maria de Jetibá no Espírito Santo - Andrade, Janice Gusmão Ferreira de (2017)
Our general objective is to investigate the deployment process and implementation of the National Plan for the Eradication of Extreme Poverty in Brazil, specifically the Plan Brazil Without Misery (PBSM), focusing the search on the immigrants descendants of pomeranians considered "people of traditional communities" in the State of Espírito Santo. This thesis is justified by the necessity of democratizing access to income and socioassistenciais services to families in extreme poverty situation of traditional communities, specifically the descendants of pomeranians. I was the social worker who made the first team of the program Include (PBSM) in the country of Santa Maria de Jetibá inEspírito Santo. We conducted a qualitative study. Our methodological process was constituted of interview, questionnaire and application form.The first National Bulletin Brazil plan Without Misery released in 2012 registered 92 families in the city. We estimate a 10% sampling of this universe for our research. We found 15 families who meet the profile, and recipient families program 09 only agreed to participate in the survey through form. The Brazil Plan Without Misery acted together to farmers in rural areas and brought several programs for working for families in the urban area. Worried about more marginal groups in society: the groups that had not been entered in the register Only, this means that many families were in public policies and social invisibility. The subject of our research work in agriculture on a family economy. Considering all our benchmark and noting that in many cases the income transfer programs are the only income of these people, we say that these tax programs promote inclusion, even precarious and marginal way, they don’t have the goal of universalizing and rather focus on the poorest among the poor. But the focusing of the PBSM was essential to locate families invisibility to the social protection system